The first psychodid (Diptera: Psychodidae: Phlebotominae) species from the Lower Eocene amber of Vastan, Gujarat, India - Solórzano Kraemer, Mónica M.; Wagner, Rüdiger (Zootaxa, 2009)
The new genus and species, Phlebotoiella eoindianensis, from the Eocene Vastan amber deposits in western India is described and illustrated. This marks the first Psychodidae to be described from Vastan amber. The relationship of this new genus is discussed as well as its biogeographic implications.